Application of Fuzzy Decision Theory in Multi Objective Logistics Distribution Center Site Selection - Wang, Kang; Wang, Xin (Informatica, 2024)
In the context of globalization and the rapid development of e-commerce, the location decision of logistics and distribution centers has become more and more critical, especially in the emerging markets, where enterprises need to take into account social responsibility and environmental sustainability while pursuing economic benefits. This study focuses on solving the multi-objective optimization problem of logistics and distribution center site selection, using fuzzy set theory and multi-objective decision analysis, combined with particle swarm optimization algorithm (PSO), an innovative fuzzy multi-objective particle swarm optimization algorithm (FMOPSO) is proposed. Through a case study of a retail company in Asia, we validate the effectiveness of FMOPSO in dealing with ambiguity and uncertainty in site selection decisions. The research process includes exhaustive data collection and preprocessing, construction of a multi-objective fuzzy decision model, and application of the FMOPSO algorithm. The results show that the A-02 address has the best performance in terms of cost-effectiveness, environmental impact, and customer service quality, and the FMOPSO algorithm demonstrates superior performance in solving this kind of complex problems, which provides a scientific basis and practical guidance for decision makers.